Engaging physicians and nurses in balanced scorecard evaluation—An implication at Palestinian hospitals and recommendations for policy makers - Amer, Faten; Kurnianto, Arie Arizandi; Alkaiyat, Abdulsalam; Endrei, Dóra; Boncz, Imre (Frontiers in Public Health, 2023)
Introduction Healthcare workers (HCWs) are seldom involved in balanced scorecard (BSC) deployments. This study aims to incorporate Palestinian HCWs in the BSC to create health policy recommendations and action plans using BSC-HCW1, a survey designed and validated based on BSC dimensions. Methodology In this cross-sectional study, the BSC-HCW1 survey was delivered to HCWs in 14 hospitals from January to October 2021 to get them involved in PE. The differences between physicians’ and nurses’ evaluations were assessed by the Mann‒Whitney U test. The causal relationships between factors were analyzed using multiple linear regression. The multicollinearity of the model was checked. Path analysis was performed to understand the BSC strategic maps based on the Palestinian HCWs’ evaluations. Results Out of 800 surveys, 454 (57%) were retrieved. No evaluation differences between physicians and nurses were found. The BSC-HCW1 model explains 22%-35% of HCW loyalty attitudes, managerial trust, and perceived patient trust and respect. HCWs’ workload time-life balance, quality and development initiatives, and managerial performance evaluation have a direct effect on improving HCWs’ loyalty attitudes (β=0.272, P<0.001; β=0.231, P<0.001; β=0.199, P<0.001, respectively). HCWs’ engagement, managerial performance evaluation, and loyalty attitudes have a direct effect on enhancing HCWs’ respect toward managers (β=0.260, P<0.001; β=0.191, P=0.001; β=0.135, P=0.010, respectively). Quality and development initiatives, HCWs’ loyalty attitudes, and workload time-life balance had a direct effect on improving perceived patient respect toward HCWs (β=254, P<0.001; β=0.137, P=0.006, β=0.137, P=0.006, respectively). Conclusion This research shows that it is important to improve low-performing indicators, such as the duration of time HCWs spend with patients, their knowledge of medications and diseases, the quality of hospital equipment and maintenance, and the inclusion of strengths and weaknesses in HCWs’ evaluations, so that HCWs are more loyal and less likely to want to leave. For Palestinian hospital managers to be respected more, they must include HCWs in their action plans and explain their evaluation criteria. Patients will respect Palestinian HCWs more if they prioritize their education and work quality, spend more time with patients, and reflect more loyalty. The results can be generalized since it encompassed 30% of Palestinian hospitals from all categories.